Epidemiological aspects of human and canine visceral leishmaniasis in State of Alagoas, Northeast, Brazil - Rocha,M. A. N. (2018)
Abstract Zoonotic visceral leishmaniasis (ZVL), caused by protozoans of the genus Leishmania, it is a worldwide of great importance disease. In the northeast region of Brazil, the state of Alagoas has an endemic status for ZVL. Thus, this work aimed to analyze the epidemiological situation of human and canine visceral leishmaniasis in Alagoas, Northeast, Brazil, from 2007 to 2013. We conducted a descriptive, observational, retrospective study using secondary data from the Notifiable Diseases Information System, the Center of Zoonosis Control of Maceió, and the Central Laboratory of Public Health of Alagoas. During the studied period, it was observed that the highest incidence of human visceral leishmaniasis was in 2011 and the lowest in 2013. On the other hand, canine visceral leishmaniasis had its highest incidence in 2007 and its lowest in 2012. Of the 55 municipalities in the State of Alagoas that showed human visceral leishmaniasis (HVL), São José da Tapera presented an average of 4.4 cases over the past five years, being classified as of intense transmission. Regarding canine visceral leishmaniasis, in the same studied period, 45,112 dogs were examined in the State, of which 4,466 were positive. It resulted, thus, in a 9.9% positivity rate. Conclusions: Our data are important because canine infection is an important risk factor for the human disease.